Anquiloglossia: desafios no diagnóstico e impacto no aleitamento materno exclusivo - Covolan, Maria Terezinha Mucheroni (2018)
Ankyloglossia is a minor congenital anomaly, characterized by alteration of the lingual frenulum which interferes in varying degrees in the tongue's movements, representing a potential risk to the success of breastfeeding. The prevalence and relationship of ankyloglossia with breastfeeding is still controversial. The lack of a universal diagnostic and classification tool makes it difficult to communicate among professionals and favors misleading behaviors that can generate distress and doubts in mothers about the quality of their milk and their ability to breastfeed. The aim of the present study was to verify the prevalence of ankyloglossia in newborns using the Bristol Tongue Assessment Tool (BTAT) and the Lingual Frenulum Protocol with Scores for Infants - NCBI (Martinelli Protocol), clearly indicating their specificities; to investigate the challenges in the diagnostic process and to evaluate the impact of ankyloglossia on exclusive breastfeeding comparing the performance of infants with and without lingual frenulum alteration. The research was carried out in two phases: the first one aimed at diagnosis and the second one, characterized by the follow-up of Exclusive Breastfeeding (SMA) in the first six months of life. The lingual frenulum of 265 newborns was evaluated before hospital discharge, following the criteria of the two methods. For the second phase the selection of the babies obeyed the following criteria: - babies with diagnosis of ankyloglossia in one of the protocols; - those with scores 5 and 6 in the Martinelli Protocol, for the "Retest"; - newborns where the absence of crying compromised the completion of the diagnosis; - babies who did not meet the above criteria and accepted the invitation for monthly breastfeeding follow-up. The prevalence was 10.9% for ankyloglossia and 6.8% for severe ankyloglossia, according to the Protocols of Martinelli and Bristol Protocol, respectively. The capability for the Martinelli Protocol, as well as the presence of images guide this instrument made possible the interpretation and use of the Bristol Protocol. The challenge to attend the consultations, presented by the mothers, shows the importance of the evaluation of the lingual frenulum before the hospital discharge. The difficulty in solving the cases suggests the need for a "Reference Center" for the treatment of ankyloglossia. The duration of exclusive breastfeeding was lower in the group with ankyloglossia, especially in the first month, suggesting that this alteration is an additional factor to many others that involves the maintenance of this practice. Early introduction of other fluids was greater in ankyloglossia and may be related to reports of discomfort that was also greater in this group.